A guardian in need of support: the enforcement of EU state aid rules. Issue 4 (3rd April 2022) - Finke, Daniel
ABSTRACT: State aid poses a threat to undistorted competition in the common market and, therefore, is rigidly regulated. However, elected political leaders have an incentive to disobey European Union (EU) regulations and grant aid in order to boost their electoral support. The European Commission is responsible for monitoring and enforcing member states' compliance with EU state aid regulation. The present article analyses the effect of domestic politics on the Commission's willingness to open a formal investigation and thus risk conflict with national governments. Specifically, it argues that the Commission is more likely to investigate, where institutional trust is strong and where ruling parties follow an interventionist economic policy.